Paraneoplastic Filiform Hyperkeratosis and Immunoglobulin-Associated Vasculitis in Myeloma Progression: A Case Report - Mathias Oymanns; Mehmet Baltaci; Aliyah Bellm; Chalid Assaf (Karger Publishers, 2021)
Multiple myeloma is a lymphoproliferative disease, which rarely presents with skin involvement or associated symptoms. Better awareness of these dermatological presentations is required for early diagnosis and to guide the patient towards appropriate therapy. We report on a patient with diffuse filiform hyperkeratosis and immunoglobulin-associated vasculitis in a severe progression of a known myeloma.